Swelling, mechanical strength, and release properties of probucol microcapsules with and without a bile acid, and their potential oral delivery in diabetes - Negrulj, R.; Mooranian, A.; Chen-Tan, N.; Al-Sallami, H.; Mikov, M.; Golocorbin-Kon, S.; Fakhoury, M.; Watts, G.; Arfuso, Frank; Al-Salami, H. (2015)
We have demonstrated a permeation-enhancing effect of deoxycholic acid (DCA), the bile acid, in diabetic rats. In this study, we designed DCA-based microcapsules for the oral delivery of the antilipidemic drug probucol (PB), which has potential antidiabetic effects. We aimed to further characterize these microcapsules and examine their pH-dependent release properties, as well as the effects of DCA on their stability and mechanical strength at various pH and temperature values. Using the polymer sodium alginate (SA), we prepared PB-SA (control) and PB-DCA-SA (test) microcapsules. The microcapsules were examined for drug content, size, surface composition, release, Micro-CT cross-sectional imaging, stability, Zeta potential, mechanical strength, and swelling characteristics at different pH and temperature values. The microencapsulation efficiency and production yield were also examined. The addition of DCA resulted in microcapsules with a greater density and with reduced swelling at a pH of 7.8 and at temperatures of 25°C and 37°C (p < 0.01). The size, surface composition, production yield, and microencapsulation efficiency of the microcapsules remained similar after DCA addition. PB-SA microcapsules produced multiphasic PB release, while PB-DCA-SA microcapsules produced monophasic PB release, suggesting more controlled PB release in the presence of DCA. The PB-DCA-SA microcapsules showed good stability and a pH-sensitive uniphasic release pattern, which may suggest potential applications in the oral delivery of PB in diabetes.